Nanostructured Si−C Composites As High-Capacity Anode Material For All-Solid-State Lithium-Ion Batteries** - Poetke, Stephanie; Hippauf, Felix; Baasner, Anne; Dorfler, Susanne; Althues, Holger; Kaskel, Stefan (Batteries & Supercaps, 2021)
Silicon carbon void structures (Si−C) are attractive anode materials for lithium-ion batteries to cope with the volume changes of silicon during cycling. In this study, Si−C with varying Si contents (28–37 %) are evaluated in all-solid-state batteries (ASSBs) for the first time. The carbon matrix enables enhanced performance and lifetime of the Si−C composites compared to bare silicon nanoparticles in half-cells even at high loadings of up to 7.4 mAh cm−2. In full cells with nickel-rich NCM (LiNi0.9Co0.05Mn0.05O2, 210 mAh g−1), kinetic limitations in the anode lead to a lowered voltage plateau compared to NCM half-cells. The solid electrolyte (Li6PS5Cl, 3 mS cm−1) does not penetrate the Si−C void structure resulting in less side reactions and higher initial coulombic efficiency compared to a liquid electrolyte (72.7 % vs. 31.0 %). Investigating the influence of balancing of full cells using 3-electrode ASSB cells revealed a higher delithiation of the cathode as a result of the higher cut-off voltage of the anode at high n/p ratios. During galvanostatic cycling, full cells with either a low or rather high overbalancing of the anode showed the highest capacity retention of up to 87.7 % after 50 cycles.
CRIS-Team Scopus Importer:2022-04-14
Keywords: all-solid-state battery; balancing; nanostructures; silicon carbon composites; thiophosphate solid electrolyte